Sociotropy and autonomy in older adults and the relationships between the personality styles, social support, and affect : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North - Craven, Gillian Mary (Massey University, 2007)
High rates of depression and anxiety are found among older adults. This study investigated the relationship between vulnerability factors and protective factors experienced among this age group. Sociotropy and autonomy are orthogonal cognitive schemata, which influence the experience, and treatment of depression and anxiety in vulnerable individuals. Both sociotropy and autonomy are related to our view of self and others in our world, so it is likely that they influence how social support (which has been identified as a protective factor against the development of depression) is used and perceived. While the concepts of sociotropy and autonomy have been studied extensively in samples of young adults, little research has been undertaken with older adults and none with a New Zealand sample. This study addressed this deficit, with a sample of 492 community-living older adults aged 65 years and older, which was obtained from the New Zealand electoral roll. The present research comprised two stages. The first stage investigated the structure of sociotropy and autonomy, and consisted of two studies. In Study 1, data obtained from the older adult sample via a postal survey, indicated that the single Sociotropy scale and the two autonomy subscales (Independence and Solitude) of the Revised Sociotropy-Autonomy Scale [SAS-Rev] (D. A. Clark, Steer, Beck, & Ross, 1995) were moderately correlated, contrary to previous findings. Principal components analyses were run on the items to examine the structure of the scales more closely. Two sociotropy subscales (Interpersonal Sensitivity and Attachment) and one autonomy scale (Independence) emerged. The scales were still weakly correlated. In Study 2, the structure of sociotropy/autonomy was examined in a student sample in order to ascertain if the difference in structure was due to age. Data obtained from 120 students living in New Zealand, via an online survey, indicated the same independent factor structure as proposed by D. A. Clark et al. (1995). Thus it is proposed that the nature of sociotropy and autonomy is different for older adults than for younger age groups. Also, for older adults, sociotropy and autonomy are not independent constructs and are less clearly differentiated than in younger age groups. Stage 2 examined the influence of the two sociotropy factors (Interpersonal Sensitivity and Attachment) and the autonomy factor (Independence) on the structure of older adults' support networks, the amount of support they receive from family and friends, and how much support they perceive to be available from family and fiends. Positive Affect and Negative Affect were also assessed, as indicators of mental well-being. Attachment was found to be a unique predictor of decreased Available Family Support, increased Available Friend Support, and increased Received Family Support. Received Friend Support was the only support predictor of increased Positive Affect. Of the sociotropy/autonomy factors, higher levels of Independence resulted in increased levels of Positive Affect, while Sensitivity predicted increased levels of Negative Affect and negatively contributed to Positive Affect. None of the sociotropy/autonomy factors moderated the relationship between Received Friend Support and Positive Affect. Implications for assessment of sociotropy/autonomy in older adults, the development of support programmes, and cognitive interventions aimed at enhancing the mental well-being of older adults are discussed. Additional studies are required to provide a more in-depth explanation of the relationships between sociotropy/autonomy and functions of social support among older adults. Suggestions are offered for how future research could further clarify the present findings.
Keywords: Depression; Independence; Support for elderly; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380106 Developmental psychology and ageing